PROTECTED NATURAL AREAS: A BRIEF HISTORY OF THE EMERGENCE OF NATIONAL PARKS AND EXTRACTIVE RESERVES - Bahia-de-Aguia, Paulo César (2013)
This article’s objective is to present a brief history of the emergence of national parks and extractive reserves as protected natural areas. For this study, a survey was done using bibliographical and documentary sources on the subject. This survey showed some aspects of the importance of protected natural areas as well as a brief history of the emergence of national parks worldwide and their implementation, and also a brief history of the emergence of extractive reserves in Brazil.